If the Fed sneezes, who catches a cold? - Luca Dedola; Giulia Rivolta; Livio Stracca (European Central Bank (ECB), 2017)
This paper studies the international spillovers of US monetary policy shocks on a number of macroeconomic and financial variables in 36 advanced and emerging economies. In most countries, a surprise US monetary tightening leads to depreciation against the dollar; industrial production and real GDP fall, unemployment rises. Inflation declines especially in advanced economies. At the same time, there is significant heterogeneity across countries in the response of asset prices, and portfolio and banking cross-border flows. However, no clear-cut systematic relation emerges between country responses and likely relevant country characteristics, such as their income level, dollar exchange rate flexibility, financial openness, trade openness vs. the US, dollar exposure in foreign assets and liabilities, and incidence of commodity exports.
Keywords: F3; F4; 330; identification of monetary shocks; international transmission; exchange rateregime; capital mobility; trilemma